2021
DOI: 10.21203/rs.3.rs-463024/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The need for nutritional assessment and interventions based on the prognostic nutritional index for patients with femoral fractures: a retrospective study

Abstract: Background The incidence of adverse perioperative outcomes in surgery for femoral fractures is quite high and is associated with malnutrition. This study aimed to identify independent factors and assess the predictive value of the prognostic nutritional index (PNI) for perioperative adverse outcomes in patients with femoral fractures. Methods This retrospective study included 343 patients who underwent surgery for a single femur fracture. Demographic characteristics, surgery and anaesthesia records, and bloo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Recent studies also showed that patients with femoral fracture needed nutritional evaluation and nutritional intervention, and PNI at admission may be a good nutritional evaluation index. 20 Furthermore, studies using other tools such as Mini-Nutritional Assessment (MNA) and Modified Vulnerability Index also proved that malnutrition in elderly patients with hip fracture was closely related to their mortality. [21][22][23] Malnutrition is a risk factor for the poor postoperative outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also showed that patients with femoral fracture needed nutritional evaluation and nutritional intervention, and PNI at admission may be a good nutritional evaluation index. 20 Furthermore, studies using other tools such as Mini-Nutritional Assessment (MNA) and Modified Vulnerability Index also proved that malnutrition in elderly patients with hip fracture was closely related to their mortality. [21][22][23] Malnutrition is a risk factor for the poor postoperative outcome.…”
Section: Discussionmentioning
confidence: 99%